The interplay of avatar identities, self-efficacy, and language practices - Chen, Julian (John Benjamins Publishing Company, 2020)
This study intends to examine English as a foreign language (EFL) learners’ attitudes toward practicing English in Second Life (SL) and to unpack the effects of avatar identities on EFL learners’ sense of self-efficacy and language practices. Nine EFL learners worldwide participated in a task-based course in SL, using avatars to carry out SL-related tasks while interacting with peers and the teacher via voice chat. Qualitative data were triangulated from multiple sources: learner reflective journals, a post-course survey, and semi-structured interviews. Three major themes emerged: (1) the effects of masked identity on learning, (2) the impact of telepresence and copresence on learning, and (3) the perceived attitudes toward avatar affinity. Findings implicate that the avatar form renders masked identities to safeguard learners’ self-efficacy and empower their language practices. It also opens up a research avenue on the impact of avatar identities on language learning and teaching in 3D virtual environments.